Annual Update in Intensive Care and Emergency Medicine 2018 (Annual Update in Intensive Care and Emergency Medicine,, 2018)
The Annual Update compiles reviews of the most recent developments in experimental and clinical intensive care and emergency medicine research and practice in one comprehensive reference book. The chapters are written by well recognized experts in these fields. The book is addressed to everyone involved in internal medicine, anesthesia, surgery, pediatrics, intensive care and emergency medicine.